2008
DOI: 10.1038/sj.onc.1211025
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin expression in metastatic breast cancer cells enhances their invasive phenotype

Abstract: Endoglin is a cell-surface adhesion protein as well as a coreceptor for transforming growth factor-b (TGF-b). It is located on endothelial and few other cells, but also found on certain tumor cells. Brain metastatic breast tumor cells derived from the MDA-MB-231 cell line heavily express endoglin in contrast to the corresponding parental ones. To clarify whether this determines their invasive phenotype, we compared their biological properties with endoglin-silenced brain-metastatic cells, lowexpressing parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 25 publications
1
45
2
Order By: Relevance
“…The reasons for these differing effects on TGF-b signaling are not known but may reflect differing mechanisms regulating the interplay between endoglin and TGF-b in squamous carcinomas versus prostate/breast carcinomas. Surprisingly, a pro-invasive role for endoglin has been reported recently in MDA-MB-231 cells in vitro (Oxmann et al, 2008), which is in direct contrast to the in vitro and in vivo findings reported here. However, it should be noted that these authors performed their scratch-wound migration and Boyden-chamber invasion assays over a 3-h period and therefore may be monitoring a short-term cellular phenotype rather than cell migration/invasion.…”
Section: Discussioncontrasting
confidence: 99%
“…The reasons for these differing effects on TGF-b signaling are not known but may reflect differing mechanisms regulating the interplay between endoglin and TGF-b in squamous carcinomas versus prostate/breast carcinomas. Surprisingly, a pro-invasive role for endoglin has been reported recently in MDA-MB-231 cells in vitro (Oxmann et al, 2008), which is in direct contrast to the in vitro and in vivo findings reported here. However, it should be noted that these authors performed their scratch-wound migration and Boyden-chamber invasion assays over a 3-h period and therefore may be monitoring a short-term cellular phenotype rather than cell migration/invasion.…”
Section: Discussioncontrasting
confidence: 99%
“…Another protein, able to induce invadopodia and also involved in EMT, is endoglin, a cell surface adhesion molecule and coreceptor for TGFβ signaling [224]. Endoglin is needed for EMT during heart development, and its expression correlates with increased invasiveness of breast cancer cells via the increased formation of invadopodia [198,225].…”
Section: Invadopodia and Their Role In Emtmentioning
confidence: 99%
“…Invadopodia have been identified in numerous cancer cell lines, including malignant melanoma, breast cancer, glioma, and head and neck cancer [193][194][195][196]. The formation of invadopodia can be initiated by various signals, for example by EGF, HGF or TGFβ-induced signal transduction [193,197,198] or by α 6 β 1 -integrin engagement [199]. Invadopodia-inducing Integrins (like α v β 3 -integrin), along with their cytoplasmic interaction partners, are positioned in the adhesive ring where they mediate adhesion.…”
Section: Podosomes and Invadopodiamentioning
confidence: 99%
“…Together, these data indicate that mutp53 docks onto Sp1 to increase ENTPD5 promoter activity. To explore whether mutp53 and ENTPD5 enhance folding and maturation of N-glycoproteins, we investigated endoglin/CD105, a coreceptor for TGFβ that is implicated in migration, invasion, and metastasis of breast and pancreatic cancer cells (19,31,32). Endoglin function relies exquisitely on protein folding in the calnexin/calreticulin cycle because endoglin mutants that colocalize with calnexin in the ER cause hereditary hemorrhagic telangiectasia (33,34).…”
Section: Entpd5 Expression Levels Correlate With Gof P53 In Human Tumormentioning
confidence: 99%